Knowledge about cholera and its prevention among household heads in a highly urbanized city in Western Philippines: a cross-sectional study - Oscares, Karen Joy S.; Pacubas, Sarah Adelaide S.; Padpad, Felb Audrey Hope G.; Paglomutan, Precious Angel A.; Panelo, Pearl Krystelle R.; Oducado, Ryan Michael Flores (Universitas Airlangga, 2024)
Introduction: Cholera remains a significant public health threat globally, but its impact can be significantly reduced with the right knowledge and correct preventive practices. Conducting a study to provide baseline data and identify knowledge gaps on cholera will benefit at-risk and vulnerable communities. This research aimed to determine the household heads' knowledge about cholera and its prevention in a barangay in the Western Philippines. Methods: A cross-sectional survey using a questionnaire was conducted in an urban barangay in Iloilo City in Western Philippines among 252 randomly selected household heads in May 2023. Data were described, and t-Test for independent samples and one-way ANOVA were used to test for differences. Results: The majority of household heads were generally knowledgeable about cholera and its prevention, but only 51.2% knew that oral rehydrating solution (ORS) could help manage symptoms of cholera. Furthermore, there was a significant difference in knowledge about cholera and its prevention based on sex (t = 2.92; p = 0.004). Conclusions: Household heads understood well and were informed of cholera and its prevention, although there were still some misconceptions. Continuous health education and knowledge assessment are recommended to raise awareness and ensure correct and timely information dissemination regarding cholera.